Considerations on the choice of experimental parameters in residual stress measurements by hole-drilling and ESPI (Fracture and Structural Integrity, 2014)
Residual stresses occur in many manufactured structures and components. Great number of investigations have been carried out to study this phenomenon. Over the years, different techniques have been developed to measure residual stresses; nowadays the combination of Hole Drilling method (HD) with Electronic Speckle Pattern Interferometry (ESPI) has encountered great interest. The use of a high sensitivity optical technique instead of the strain gage rosette has the advantage to provide full field information without any contact with the sample by consequently reducing the cost and the time required for the measurement. The accuracy of the measurement, however, is influenced by the proper choice of several parameters: geometrical, analysis and experimental. In this paper, in particular, the effects of some of those parameters are investigated: misknowledgment in illumination and detection angles, the influence of the relative angle between the sensitivity vector of the system and the principal stress directions, the extension of the area of analysis and the adopted drilling rotation speed. In conclusion indications are provided to the scope of optimizing the measurement process together with the identification of the major sources of errors that can arise during the measuring and the analysis stages.
Keywords: Electronic Speckle Pattern Interferometry (ESPI)